2006
DOI: 10.3122/jabfm.19.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Group Visits: A Qualitative Review of Current Research

Abstract: Over the past 2 decades, chronic illness has become a pressing public health issue. Over 90 million Americans suffer from a chronic disease, accounting for more than 75% of the nation's total medical care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
175
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(176 citation statements)
references
References 30 publications
1
175
0
Order By: Relevance
“…6 They provide more time for self-management education and skill building and may reduce perceived barriers to behavior change. 6 Group visits can improve patient satisfaction by increasing patients' trust in providers and promoting patients' engagement in their care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 They provide more time for self-management education and skill building and may reduce perceived barriers to behavior change. 6 Group visits can improve patient satisfaction by increasing patients' trust in providers and promoting patients' engagement in their care.…”
Section: Discussionmentioning
confidence: 99%
“…6 They provide more time for self-management education and skill building and may reduce perceived barriers to behavior change. 6 Group visits can improve patient satisfaction by increasing patients' trust in providers and promoting patients' engagement in their care. 6,7 Studies have demonstrated group visit programs can reduce emergency department visits, visits to specialists and hospital admissions and the associated costs of care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations